(untitled) (The Peerian Journal, 2023)
The aim of this research was to explore the depths of the link between strategic vigilance and strategic effectiveness , with the presence of information quality as a mediating variable, where a sample of tourism companies operating in several Iraqi governorates was selected. The board of directors working in those companies, and the research data was collected using the questionnaire form, This served as the primary method for gathering information . The results drawn from the research revealed that there is a correlation and impact of strategic vigilance and information quality on strategic performance . It also concluded that there is a role for information quality as a mediating variable between strategic vigilance and strategic performance